The emergence of Vibrio pathogens in Europe: ecology, evolution, and pathogenesis (Paris, 11–12th March 2015) - Roux, Frédérique Le; Wegner, K. Mathias; Baker-Austin, Craig; Vezzulli, Luigi; Osorio, Carlos R.; Amaro, Carmen; Ritchie, Jennifer M.; Defoirdt, Tom; Destoumieux-Garzón, Delphine; Blokesch, Melanie; Mazel, Didier; Jacq, Annick; et al. (Frontiers in Microbiology, 2015)
Global change has caused a worldwide increase in reports of Vibrio-associated diseases with ecosystem-wide impacts on humans and marine animals. In Europe, higher prevalence of human infections followed regional climatic trends with outbreaks occurring during episodes of unusually warm weather. Similar patterns were also observed in Vibrio-associated diseases affecting marine organisms such as fish, bivalves and corals. Basic knowledge is still lacking on the ecology and evolutionary biology of these bacteria as well as on their virulence mechanisms. Current limitations in experimental systems to study infection and the lack of diagnostic tools still prevent a better understanding of Vibrio emergence. A major challenge is to foster cooperation between fundamental and applied research in order to investigate the consequences of pathogen emergence in natural Vibrio populations and answer federative questions that meet societal needs. Here we report the proceedings of the first European workshop dedicated to these specific goals of the Vibrio research community by connecting current knowledge to societal issues related to ocean health and food security.